The 1930s and the 1980s parallels and differences - Kindleberger, Charles Poor 1910-2003 (Asean Economic Research Unit, Institute of Southeast Asian Studies, 1989)
This paper describes how financial crises come about, and analyses in particular the circumstances that led to the crises of the 1930s and 1980s. It concludes with suggestions on how to enhance world economic stability